Surface structurization and control of CuS particle size by discharge mode of inductively coupled plasma and vapor-phase sulfurization. (7th November 2018) - Choi, Daehan; Kim, Tae-Wan; Shahzad, Rauf; Park, Hyeji; Yeom, H J; Kim, J H; Seong, D J; Kang, Sang-Woo; Yoon, Euijoon; Lee, Hyo-Chang
Abstract: Copper sulfide (CuS) nanoparticle films with different nanoparticle sizes were fabricated using an inductively coupled plasma (ICP) and a vapor-phase sulfurization method. First, the ICP is applied to a thin copper film to obtain a copper nanoparticle film, based on the plasma–surface interactions through the ion bombardment on the film. The fabrication of the Cu nanoparticles revealed that their size and spatial distribution depend on the discharge mode of the ICP and plasma irradiation time. From the measurements of the plasma density, optical emission spectrum, and ion flux energy distribution function, it was found that the inductive mode of the ICP, compared to the capacitive mode of the ICP, is efficient at fabricating the uniform nanoparticle film due to the optimal plasma potential and high ion flux with narrow ion energy distribution. The Cu nanoparticles are then transformed to CuS nanoparticles through vapor-phase sulfurization. For the hydrophobicity application of the CuS nanoparticle film, the contact angles of the CuS nanoparticle films were measured and compared with those of other thin films, such as SiO2 and bulk CuS. The contact angle of the CuS nanoparticle film, fabricated through the plasma–surface interactions and sulfurization, was significantly higher than that of other thin films owing to the hydrophobic surface of the CuS with the nanoparticle structure.